Técnicas para otimização de conversores da família boost com alto ganho de tensão e alto rendimento aplicados à célula a combustível - Tiburski, Mateus José (2019)
In this work, it is proposed methodologies for design optimization of high gain boost static converters applied to fuel cells. In this aplication, two types of boost converters are evaluated. The first one is based on the conventional boost topology, reported in literature as an unusual converter for high gain applications due to limitations caused by the resistive elements present in the components. Therefore, a method is proposed, aiming to analyze the operating limits of this converter, through mathematical analyses which estimate its losses and volumes, and the use of techniques that reduce the series resistances in the converter’s components. For the second, based on the cascade boost topology, or just boost cascaded, the high gain is not a limiting factor, but rather the low efficiency associated with the high number of components, which makes this converter unattractive when high voltage gain applications are required. Thus, a methodology is developed, aiming to find optimal solutions by scanning converter’s parameters such as, switching frequency, inductor current ripple, variation of the current density in the conductor and the intermediate voltage of the converter. For this study, a database with several options of magnetic cores, semiconductors, sinks and capacitors are analyzed so that different projects possibilities are tested, according to the optimization objective (efficiency and volume). Finally, simulation results expose the best solutions for efficiency and volume for each converter, indicating the possibility of obtaining a high gain for the conventional boost converter and high throughput or low volume for the boost cascaded converter.